INVESTIGATING COMMUNITY READINESS THROUGH IT INFRASTRUCTURE, ONLINE TRANSACTIONS, AND COMMUNITY BEHAVIOR FOR URBAN VILLAGE DIGITAL TRANSFORMATION IN PALEMBANG - Berliana Inasti; Darius Antoni; Agustina Heryati (Jurnal Kecerdasan Buatan dan Teknologi Informasi, 2026)
The rapid development of information technology has encouraged digital transformation in various sectors, including public administrative services at the urban village level. However, the successful implementation of digital transformation depends not only on government readiness and technological infrastructure but also on the readiness of the community as the primary users of digital services. This study aims to evaluate community readiness toward digital transformation and design a web-based digital administrative service architecture for Sukamaju Urban Village, Palembang City, using the TOGAF ADM framework. The study employed a descriptive quantitative approach involving 395 respondents selected using the Slovin formula with a 5% margin of error. Data were collected through closed-ended questionnaires based on a 5-point Likert scale and analyzed using the E-Readiness approach through three main variables: Information Technology Infrastructure, Online Transactions, and Community Behavior. The results indicate that the Information Technology Infrastructure variable achieved the highest mean score of 4.32 (Very Ready), followed by Community Behavior with a mean score of 4.20 (Ready), and Online Transactions with a mean score of 4.11 (Ready). These findings suggest that the Sukamaju Urban Village community possesses a high level of readiness to support digital transformation in administrative services. Based on these findings, a web-based digital administrative service architecture was proposed using TOGAF ADM phases, including Architecture Vision, Business Architecture, Information Systems Architecture, and Technology Architecture. The proposed system is expected to improve service efficiency, reduce manual administrative processes, and support sustainable digital transformation at the urban village level.